Metabolomic Changes in Serum of Children with Different Clinical Diagnoses of Malnutrition. Issue 12 (2nd November 2016) - Di Giovanni, Valeria; Bourdon, Celine; Wang, Dominic X; Seshadri, Swapna; Senga, Edward; Versloot, Christian J; Voskuijl, Wieger; Semba, Richard D; Trehan, Indi; Moaddel, Ruin; Ordiz, M Isabel; Zhang, Ling; et al.
Abstract: Background: Mortality in children with severe acute malnutrition (SAM) remains high despite standardized rehabilitation protocols. Two forms of SAM are classically distinguished: kwashiorkor and marasmus. Children with kwashiorkor have nutritional edema and metabolic disturbances, including hypoalbuminemia and hepatic steatosis, whereas marasmus is characterized by severe wasting. The metabolic changes underlying these phenotypes have been poorly characterized, and whether homeostasis is achieved during hospital stay is unclear. Objectives: We aimed to characterize metabolic differences between children with marasmus and kwashiorkor at hospital admission and after clinical stabilization and to compare them with stunted and nonstunted community controls. Methods: We studied children aged 9–59 mo from Malawi who were hospitalized with SAM ( n = 40; 21 with kwashiorkor and 19 with marasmus) or living in the community ( n = 157; 78 stunted and 79 nonstunted). Serum from patients with SAM was obtained at hospital admission and 3 d after nutritional stabilization and from community controls. With the use of targeted metabolomics, 141 metabolites, including amino acids, biogenic amines, acylcarnitines, sphingomyelins, and phosphatidylcholines, were measured. Results: At admission, most metabolites (128 of 141; 91%) were lower in children with kwashiorkor than in those with marasmus, with significant differences in several amino acids and biogenic amines, including those of the kynurenine-tryptophan pathway. Several phosphatidylcholines and some acylcarnitines also differed. Patients with SAM had profiles that were profoundly different from those of stunted and nonstunted controls, even after clinical stabilization. Amino acids and biogenic amines generally improved with nutritional rehabilitation, but most sphingomyelins and phosphatidylcholines did not. Conclusions: Children with kwashiorkor were metabolically distinct from those with marasmus, and were more prone to severe metabolic disruptions. Children with SAM showed metabolic profiles that were profoundly different from stunted and nonstunted controls, even after clinical stabilization. Therefore, metabolic recovery in children with SAM likely extends beyond discharge, which may explain the poor long-term outcomes in these children. This trial was registered at isrctn.org as ISRCTN13916953.